Simple immunosensor for ultrasensitive electrochemical determination of biomarker of the bone metabolism in human serum - Chang, Qiang; Huang, Jie; He, Liming; Xi, Fengna (Frontiers in Chemistry, 2022)
Ultrasensitive and selective determination of biomarker of bone metabolism in serum is crucial for early early screening, timely treatment, and monitoring curative effect of osteoporosis, which is a silent disease with serious health threat. Immunoassay with simple sensing interface and ultrahigh sensitivity is highly desirable. Herein, a simple electrochemical immunosensor is demonstrated based on gold nanoparticles (AuNPs) electrodeposited on chitosan-reduced graphene oxide (CS-G) composite modified electrode, which can achieve sensitive determination of the important biomarker of bone metabolism, bone gamma-carboxyglutamate protein (BGP). To overcome the agglomeration of graphene and introduce a biocompatible matrix with functional amino groups, CS-G is firstly prepared and modified on the supporting glassy carbon electrode (GCE). Then, AuNPs are electrodeposited on CS-G through their interaction between amine groups of CS. The immobilized AuNPs provide numerous binding sites to immobilize anti-BGP antibodies (AbBGP). The specific recognition between BGP and AbBGP results in a reduction in the mass transfer of the electrochemical probe (Fe(CN)63-/4-) in solution, leading to a reduced electrochemical signal. Based on this mechanism, fast and ultrasensitive electrochemical detection of BGP is achieved when the concentration of BGP ranges from 100 ag/mL to10 μg/mL with a limit of detection (LOD) of 20 ag/mL (S/N = 3). The determination of BGP in human serum is also realized with high reliability.